2014
DOI: 10.1002/aur.1354
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the Korean Version of the PEERS® Parent‐Assisted Social Skills Training Program for Teens With ASD

Abstract: Impaired social functioning is a hallmark feature of autism spectrum disorder (ASD), often requiring treatment throughout the life span. PEERS(®) (Program for the Education and Enrichment of Relational Skills) is a parent-assisted social skills training for teens with ASD. Although PEERS(®) has an established evidence base in improving the social skills of adolescents and young adults with ASD in North America, the efficacy of this treatment has yet to be established in cross-cultural validation trials. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
121
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 48 publications
15
121
2
2
Order By: Relevance
“…Four RCTs Laugeson et al 2009;Schohl et al 2014;Yoo et al 2014), three quasi-experimental pre-post designs with a control group Ozonoff and Miller 1995;Turner-Brown et al 2008), four quasiexperimental pre-post designs without a control group (Hillier et al 2007(Hillier et al , 2011Liu et al 2013;Tse et al 2007), one randomised complete block design study (Mandelberg et al 2014) and one single-case multiple baseline study (Mitchel et al 2010) were identified.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four RCTs Laugeson et al 2009;Schohl et al 2014;Yoo et al 2014), three quasi-experimental pre-post designs with a control group Ozonoff and Miller 1995;Turner-Brown et al 2008), four quasiexperimental pre-post designs without a control group (Hillier et al 2007(Hillier et al , 2011Liu et al 2013;Tse et al 2007), one randomised complete block design study (Mandelberg et al 2014) and one single-case multiple baseline study (Mitchel et al 2010) were identified.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…PEERS involves 12-14 weekly sessions, with each session lasting 90 min and typically includes a parent or caregiver. Four studies evaluating PEERS used an RCT design (Laugeson et al 2009;Gantman et al 2012;Schohl et al 2014;Yoo et al 2014), and each of these included a wait-list control group. One study employed a quasi-experimental pre-post design in which participants were not randomly assigned to their conditions and there was no control group ).…”
Section: Programme For the Education And Enrichment Of Relational Skillsmentioning
confidence: 99%
See 3 more Smart Citations